Analisis Kesulitan Belajar Bahasa Arab pada Santri Nurul Huda Kartasura - Abid Nurhuda (Al-Fusha : Arabic Language Education Journal, 2022)
Among the many languages, Arabic has a special feature in the form of structure, vocabulary, and grammar. There are many students who still stumble in reading, find it difficult to speak, write, and listen as experienced by students of Nurul Huda Kartasura so the purpose of this article was to analyze their difficulties in learning Arabic. The method used in this article was descriptive qualitative with observation, documentation, and interviews as data collection techniques. The problem of learning Arabic for the students of Nurul Huda Kartasura was found in linguistic factors which included pronunciation, sentence structure, vocabulary, morphology, and syntax. While other factors were non-linguistic which included low interest, individual differences, and time constraints. These two inhibiting factors often surround Arabic students who become obstacles in learning Arabic and need more attention to overcome both.